Contestation of Perspectives Toward Suicide in The Film Monsieur Lazhar (2011) by Philippe Falardeau - Tesya Imanisa Setiadi; Wening Udasmoro; Hayatul Cholsy (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. Suicide is one of the causes of death that occurs in a global scope but always causes divisive perspectives in various circles of society. For most people, suicide is a taboo topic, but not for other groups. The film Monsieur Lazhar (2011) is a film that shows the different perspectives between different age groups, namely the adult age group and the young age group, on a suicide that occurred at an elementary school in Montreal, Canada. This study aims at determining the different perspectives of the two different parties on suicide and the reasons for these differences in views. Pierre Bourdieu’s Champ de Force theory is the lens used in this research. The difference in perspective is influenced by the disposition system which Bourdieu calls the habitus. Habitus operates in a realm (champ). In the film, the domain in question is school. Meanwhile, Durkheim’s theory of suicide was chosen to determine the relationship of social problems to suicide. The method used in this research is content analysis. The data used are the chronological text of the scenes and the transcript of the conversations from the film. From the research, it was found that the school, which is the adult age group, has a counter and stigmatic view of suicide, reinforced by perceptions of psychological problems and social taboos. Meanwhile, students, who are in the young age group, tend to view suicide as a problem related to personal aspects and personal experiences so that they do not have a judgmental attitude like the school. Keywords : Suicide, Contestation, Realm, Perspective, Habitus